Framing Gerakan Islam Urban dalam Perspektif Komunikasi Islam: Studi Komparasi Teori Sosial Menurut Charles Tilly, Alberto Melucci, Olivier Roy dan Asef Bayat - Achmad Muzammil Alfan Nasrullah (ALAMTARA, 2025)
This research is based on the increasingly complex socio-religious reality in the era of urbanization and globalization, when Islamic movements are no longer merely understood as spiritual expressions, but also as social phenomena that shape collective identity, solidarity, and new patterns of interaction in the public sphere. The focus of this study is to examine how the social theories developed by Charles Tilly, Alberto Melucci, Olivier Roy, and Asef Bayat are able to frame the dynamics of contemporary Islamic movements, particularly in the context of urban societies and global change. Through a descriptive qualitative approach based on literature studies, data was collected from primary and secondary sources, then analyzed using Robert N. Entman's framing model. This analysis covers four main dimensions, namely problem definition, cause tracing, moral assessment, and solutions offered from the theoretical frameworks of the four thinkers. The results of the study show that Tilly's theory of mobilization and collective action repertoire, Melucci's concept of collective identity, Roy's idea of the de-territorialization of religion, and Bayat's idea of post-Islamism complement each other in explaining the process of transformation of Islamic movements that are increasingly adaptive, pragmatic, and transnational in nature. The findings of this study confirm that urban Islamic movements are not only a reaction to modernity, but also an active effort to construct meaning, legitimacy, and social strategies amid the tide of global change. The main contribution of this study lies in enriching the theoretical framework regarding Islamic social movements, while also providing practical implications for strengthening moderation, developing cross-identity dialogue, and formulating public policies that are more sensitive to contemporary religious dynamics.